Steam Content in Integrated Science Learning Model Project Based Learning (PjBL) In Madrasah Ibtidaiyah - Musa, Muhammad Maskur; Annur, Aan Fadia; Khusna, Syafa’atul; Kusumawati, Putri Rahadian Dyah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
21st Century Learning encourages students to have the skills needed for life in the future. One learning approach that is relevant to 21st Century skills is Science, Technology, Engineering, Art and Mathematics or STEAM. STEAM-loaded learning can be applied from basic education to higher education. This study aims to analyze the content of STEAM in science learning for plant generative reproduction in Class V Madrasah Ibtidaiyah Mumtaza Islamic School, South Tangerang City which is integrated with the Project Based Learning (PjBL) learning model. The method used in this research is descriptive qualitative with data collection techniques in the form of interviews, observations and documentation. The results of the study show that in fact, in learning science in Class V, integrated PjBL, which looks simple, already contains the STEAM component. The STEAM components contained are: (1) Science is seen when students identify the flower part, (2) Technology is in simple technology, namely the scissors used by students, (3) Engineering in the form of students' techniques in making circles and attaching flower parts, (4) Art contained when students decorate their work, and (5) Mathematics is seen when students make a circle with a certain diameter.